A guide to research for podiatrists - Campbell, Jacquelyn Andrea (M & K Update Ltd., 2007)
It is constantly suggested that, as podiatrists, we need to research, but what does this really mean? This question can be particularly problematic in a profession such as podiatry, where there has not been a strong research basis for our practice in the past. Information is no longer accepted at face value, but instead is scrutinised, criticised, questioned and used to raise other questions. Podiatrists are being prepared to understand, use and undertake their own research. The book will appeal to podiatry practitioners, lecturers and students. It is based on a popular series of articles that.